Problems of ensuring the preservation of historical and documentary heritage (archival aspect) (Journal of history, 2021)
One of the most important tasks facing the archives is the preservation of historical and documentary heritage, since they are of both historical and scientific value. Ensuring the preservation of historical and cultural heritage includes a whole range of measuresthis is the protection of the integrity of archival documents, the guarantee of their safety. These are: the construction of buildings, the creation of regula tory storage conditions, the use of special storage facilities, rational placement of documents, restoration, state accounting. The factors (physicochemical, mechanical, biological) that influenced the aging and destruction of documents are considered.An important work that is constantly carried out in the archives is the restoration of documents. In order to preserve the documentary information in case of loss or damage, an insurance fund is created. Therefore, to ensure longterm preservation, the archive solves 3 tasks: creating storage conditions, restoration and creation of an insurance fund. Much attention is paid to these problems of the archival industry of the RK.Key words: Preservation of documents, national archi